CHEMICAL COMPOSITION AND ANTIBACTERIAL ACTIVITY OF ESSENTIAL OIL OF GEDEBONG BERRIES (Piper aduncum L.) - Yuliasri Jamal; Andria Agusta; Praptiwi . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The distillation of dry powder of gedebong berries (Piper aduncum L.) resulted approximately 1.55% colorless essential oil. GC-MS analyses detected 63 components which consisted of 5.74 % monoterpene, 2.84 % monoterpene alcohol, 14.61 % sesquiterpene alcohol, 56.28 % phenyl propenoid and the other minor components about 20.35 %. Although the minor components were known as antibacterial agents, the overall essential oil did not show their activities againts pathogenic bacteria i.e. Klebseilla sp., Aeromonas hydrophilla, Pseudomonas pseudomalai, Pseudomonas aurogenusa, Salmonella enteritidis, Salmonella typhosa dan Streptococcus aureus.Keyword : Piper aduncum L., essential oil, antibacterial agent